“SAVE MERATUS”, THE MOTTO OF THE SPIRIT CONSCERVING NATURE AND ANCIENT TRADITION IN HULU SEUNGAI TENGAH REGENCY - Berry Nahdian Forqan; Septi Ariadi; Bagong Suyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Global environmental issues are in the spotlight of various parties in keeping the earth sustainable. As happened in Hulu Sungai Tengah district, by raising the slogan "save meratus" so that people are aware and care about natural threats that have a domino effect on various aspects of life. The slogan "save meratus" was able to enlighten the public in understanding the importance of preserving nature in order to remain sustainable, especially for the people in Hulu Sungai Regency. This study aims to analyze when and to what extent the slogan "save meratus" appears on the surface in enlightening the public about nature conservation. The method in this study uses discourse analysis. Data collection is done by looking at what media are campaigning for the #savemeratus symbol. The results of this study see that the #savemeratus symbol has entered various media, both social media and news media. The #savemeratus symbol has exceeded the initially expected limit. Through this symbol, the community is enlightened about the issue of the Meratus Mountain area and the importance of protecting the environment so that it remains sustainable.